Circulating MicroRNAs as Potential Molecular Biomarkers in Pathophysiological Evolution of Pregnancy. (17th July 2016) - Cretoiu, Dragos; Xu, Jiahong; Xiao, Junjie; Suciu, Nicolae; Cretoiu, Sanda Maria
Abstract : MicroRNAs represent nonprotein coding small RNA molecules that are very stable to degradation and responsible for gene silencing in most eukaryotic cells. Increased evidence has been accumulating over the years about their potential value as biomarkers for several diseases. MicroRNAs were predicted to be involved in nearly all biological processes from development to oncogenesis. In this review, we address the importance of circulating microRNAs in different conditions associated with pregnancy starting with the implantation period to preeclampsia and we shortly describe the correlation between placental circulating miRNAs and pregnancy status. We also discuss the importance of microRNAs in recurrent abortion and ectopic pregnancy.